MENINGKATKAN KETERAMPILAN MENULIS TEKS ARGUMENTASI MENGGUNAKAN MEDIA POSTER DIGITAL PADA SISWA KELAS XI SMA NEGERI 3 MEDAN - Sari, Vivi Novita; Srikandi, Cut Novita; Simamarmata, Natalia (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This research aims to improve the argumentative text writing skills of class XI students at SMA Negeri 3 Medan using digital poster media. Many students experience difficulty in composing a good argumentative text structure, using appropriate language, and conveying arguments logically and persuasively. The results of this two-cycle Classroom Action Research (CAR) project showed a significant increase in students' writing skills. The proportion of students who completed their education increased from 33.33% at the beginning of the pre-cycle phase to 58.33% during cycle I, and then to 86.11% at the end of cycle II. These results prove that digital poster media is effective in improving the quality of students' writing, because it motivates them to learn and makes it easier to understand the material. Digital poster media can be used as an effective alternative to improve students' argumentative text writing skills